Tindak Pidana Memperniagakan Tumbuhan dan Satwa Liar dalam Perspektif Fikih Jinayah dan Undang-Undang Nomor 5 Tahun 1990: The Crime of Trafficking in Wild Plants and Animals in the Perspective of Jurisprudence and Law No. 5 of 1990 - Aswanto Muhammad Takwi Hede; Jamaluddin, Jamaluddin; Adrian, Adrian (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This research aims to find out how the criminal act of trading wild plants and animals in the perspective of jinayah fiqh and law no. 5 of 1990. This research method is library research. Library research is a data collection technique that involves an in-depth study of books, literature, notes that are relevant to the problem under study, this research approach method is normative juridical and comparative approach. The results of this research are: First, in jinayah fiqh, the type of criminal act of trading wild plants and animals falls into the takzir category, where the punishment is determined by the ruler or government. Meanwhile, according to Law No. 5 of 1990, Article 40 states that the maximum imprisonment of 5 years and a maximum fine of 100,000,000.00 for intentional violations, as well as a maximum imprisonment of 1 year and a maximum fine of Rp. 50,000,000.00 for violations due to negligence. Second, the similarities between the two are both aimed at protecting the preservation of nature and punishing perpetrators who harm the environment who trade in protected plants and wildlife, while the significant differences between the two between jinayah fiqh and the Law include aspects of the legal basis, approach in determining penalties, emphasis on moral values, and the process of applying different laws. The implication of this research is that it is expected to be a consideration for the community.